Audit Sistem Informasi Penerimaan Murid Baru Menggunakan Framework COBIT 5.0 Pada Sekolah Islam Al Azhar Summarecon Serpong - Nia Wahyuningsih; Narti Narti (Dirgamaya: Jurnal Manajemen dan Sistem Informasi, 2023)
This research aims to measure and evaluate the governance of the new student admission information system at Al Azhar Islamic School Summarecon Serpong using the COBIT 5.0 framework. The audit results indicate that several domains, such as change management and performance monitoring, have achieved the expected targets. However, the overall maturity level of the governance still needs improvement. Nevertheless, the implementation of the new student admission information system has been carried out with a comprehensive and systematic approach. Recommended solutions include improving program and project management, enhancing internal services, and achieving the desired maturity levels. In this study, the audit findings show that the new student admission information system at Al Azhar Islamic School Summarecon Serpong has achieved a level of F, indicating a complete approach and full achievement in the performance scale. However, there are still areas that require improvement, with the highest gap observed in program and project management. By addressing the unachieved processes and implementing the recommended solutions, it is expected that the new student admission information system will become more effective and efficient in supporting the admission process at Al Azhar Islamic School Summarecon Serpong.